READING SHUSAKU ENDO'S SILENCE WITH AN ESCHATOLOGICAL IMAGINATION. - Enright, Lyle (Renascence)
In this article, the author focuses on the book "Silence" by Shusaku Endo is presented. It mentions that Portuguese Catholic priest's experience with persecution in Edo-era Japan, and states the book "Mysterium Paschale" by Hans Urs von Balthasar. It also mentions Balthasar's provide outline of centrality of the resurrection to the Christian narrative in his book.